Enfermedad inflamatoria crónica del intestino delgado del perro: comparación de índices de actividad - García-sancho, Mercedes; Rodríguez-franco, Fernando; Sainz Rodríguez, Ángel (Revista Complutense de Ciencias Veterinarias, 2009)
Clinical assessment of disease activity has been described in canine inflammatory bowel disease (IBD). In this study, 44 dogs with lymphocytic-plasmacytic enteritis were evaluated following the canine IBD activity index (CIBDAI) reported by Jergens (small and large intestine) together with our new index based on the Jergens index, and specifically modified for small intestine disease. A reevaluation of both indeces after medical and dietary therapy was performed in 14 dogs. Comparison of indeces revealed a more reliable measure of clinical signs when the specific small intestine index was applied.